2014
DOI: 10.1161/circulationaha.114.006971
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis of Pulmonary Hypertension

Abstract: 1820T here has been an increased recognition of pulmonary hypertension (PH) in clinical practice over the past 30 years. It is likely that this rise in PH diagnoses is attributable to multiple factors, including increased awareness by clinicians, the routine use of diagnostic tools such as Doppler echocardiography, and the availability and marketing of the many PH-specific drugs.1 Although the increased awareness of the disease should be viewed as a favorable development, the unintended consequences include ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 66 publications
3
59
0
Order By: Relevance
“…This contrasts with the etiology of left heart failure patients, which is usually due to intrinsic LV dysfunction rather than LV pressure overload. In contrast, PAH is by definition a pressure overload state 46. A second reason to believe that colchicine might be beneficial in the RV failure associated with PAH is the finding that colchicine reduces adverse pulmonary vascular remodeling (Figure 6) in addition to its direct beneficial effect on RV function through increased JPH2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the etiology of left heart failure patients, which is usually due to intrinsic LV dysfunction rather than LV pressure overload. In contrast, PAH is by definition a pressure overload state 46. A second reason to believe that colchicine might be beneficial in the RV failure associated with PAH is the finding that colchicine reduces adverse pulmonary vascular remodeling (Figure 6) in addition to its direct beneficial effect on RV function through increased JPH2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Growing evidence suggests that pulmonary arterial compliance plays a critical role in the pathogenesis of PAH and right ventricular failure. 3 Decreased pulmonary arterial compliance causes premature reflection of waves from the distal pulmonary vasculature, leading to increased pulsatile right ventricular afterload and altered right ventricular-pulmonary artery (RV-PA) coupling.…”
mentioning
confidence: 99%
“…This showed that pulmonary hypertension occurs in the smokers by added mechanisms to that caused by COPD. Jugular venous pressure was looked after in this study as raised jugular venous pressure is usually found in patients with pulmonary hypertension and should be looked early for proper evaluation of the patients [14].…”
Section: Discussionmentioning
confidence: 99%